Functional Restriction for the Fear of Falling In Family Caregivers. Issue 27 (July 2015) - Shen, Jing; Hu, Fangke; Liu, Fucun; Tong, Peijian; Chebli., Caroline
<x xml:space="preserve">Abstract</x> Abstract Hip fractures often result from falls, and most family caregivers fear another fall. This study aimed to assess this fear in family caregivers and analyze its influence on functional recovery. This study was retrospectively performed by interview at the clinic or through telephone contact. The Falls Efficacy Scale International (FES-I) was used to assess fall-related feelings of patients and their family caregivers. Of the 539 patients studied, hip fracture was caused by a fall in 467 (86.6%). The mean FES-I value of the family caregivers was significantly lower than that of the patients (85.39 versus 99.02, P < 0.001). The mean patient functional recovery score (FRS) was 68.41. A fracture caused by a fall and recurrent fall-related fractures both reduced caregiver FES-I scores. The difference between patient and caregiver FES-I scores showed a significant positive correlation with the FRS (P < 0.001). Family caregivers were more concerned about falls than were patients. Furthermore, a greater difference in the fall-related reaction between caregivers and patients was associated with greater adverse effects on rehabilitation.